Futures thinking in Asia and the Pacific why foresight matters for policy makers. - Asian Development Bank.; Joint author;Editor. ([Manila] Asian Development Bank, 2020)
This publication provides updated economic forecasts for Asia and the Pacific, taking into consideration the impact of coronavirus disease (COVID-19).
Keywords: Economic forecasting -- Asia; Economic forecasting -- Pacific Area; Electronic books